Pooled Analysis of the Efficacy and Safety of Video Capsule Endoscopy in Patients with Implantable Cardiac Devices - Rabih Tabet; Najib Nassani; Boutros Karam; Youssef Shammaa; Philippe Akhrass; Liliane Deeb (Canadian Journal of Gastroenterology and Hepatology)
Background. To date, video capsule endoscopy (VCE) is still contraindicated by the FDA and the main manufacturers of Cardiac Implantable Electronic Devices (CIED) in patients with CIED, given a theoretical electromagnetic interference and possible device malfunction. Objectives. The objective of this study was to assess the safety profile and efficacy of VCE in patients with implantable cardiac devices through analyzing the risk of mutual interference. Methods. A systematic review of PubMed, Web of Science, and Embase databases was conducted. Peer-reviewed original articles, published in the English language and containing “capsule endoscopy” AND “pacemaker”, “defibrillator” OR “left ventricular assist device” as keywords, were selected. Studies performed in vitro, isolated case reports, and abstracts/posters were excluded. Results. A total of 735 VCE procedures were performed in patients with cardiac devices in various clinical settings. Cardiac events were not seen in any case. Interference on capsule images transmission was noted in 5 cases (left ventricular assist device (LVAD)) where few images were lost when the capsule was closest to the device. Finally, interference between capsule and telemetry leads was noted in 6 cases (4 Permanent Pacemakers (PPM), 2 Implantable Cardioverter-Defibrillator (ICD)) leading to image artifacts. Discussion. Adverse cardiac events were not seen in any study. Loss of images occurred when the VCE was in proximity to the device (only with LVAD) or after telemetry leads installation without affecting the completion rate and diagnostic yield of VCE. Conclusion. VCE is safe and remains efficient in patients with cardiac devices. If cardiac monitoring is required, wired systems are preferable.